HIGHWALL SLOPE STABILITY ANALYSIS USING DISTINCT ELEMENT METHOD AND LIMIT EQUILIBRIUM METHOD - INDIRAWATI (NIM : 12106019); Pembimbing : Prof. Dr. Ir. Irwandy Arif, M.Sc., DESTIEN
Instability of a slope will result in the collapse of the rock around the excavation site. For that reason a slope stability analysis is needed to anticipate the possibility of avalanches on the slopes, so that the sustainability of the mining process and the health and safety of both labor and equipment can be guaranteed. Lowwall slope stability analysis was conducted on a cross-section taken from Pit 8A, one pit mining in the East Block, PT. Indominco Mandiri (IM). In highwall slope, slope direction of bedding planes have opposite slopes, the avalanche potential will be influenced by the presence of geological structures in addition to the field of bedding planes and rock weathering rates. In this case, the modeling is done by using the limit equilibrium method through software SLIDE version 5.0 of Rocscience and by using the distinct element method through software UDEC (Universal Distinct Element Code) from Itasca to analyze the slope stability of the possibility of avalanche bow through the safety factor and to submit recommendations of safe slopes. From processing and data analysis which includes the distribution of displacement, stress distribution and the safety factor, it is found that there are several points of observation which are less steady. Safety factor on the slopes is the average value of 1.4611. Therefore it is necessary to change the slope geometry that will be recommended.